GEOCHEMICAL CHARACTERISTICS OF ECLOGITES FROM NORTHERN QAIDAM BASIN, CENTRAL CHINA - Xunfei Li; Zhiqiang Wang (Геодинамика и тектонофизика, 2017)
The occurrence of high-pressure and ultrahigh-pressure eclogites in the northern border of Qaidam basin in central China indicates the existence of a 350 km orogenic belt. These eclogites provide constraints for reconstructing the tectonic evolution history in this region. In this study, we analyzed nine eclogites sampled from the Xitieshan area, for their major and trace element abundances as well as 143Nd/144Nd isotopic ratios to investigate the factors controlling geochemical compositions of these eclogites and to infer the tectonic evolution in this region.